PENGARUH GAYA KEPEMIMPINAN, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN - Martinus Buulolo (JURNAL AS-SAID, 2021)
The provision of compensation will foster morale for employees, and encourage employee performance to continuously improve more optimal performance according to the ability of employees in their respective fields. This study is very relevant to determine the effect of leadership style and compensation on employee performance. The analysis of this study is to test the variables of leadership style, and compensation statistically partial test and simultaneous test. The method used in this study uses descriptive quantitative methods, using questionnaires and observations. To obtain research data using a population of 32 respondents, and sampling using saturated sampling or saturated samples where all members of the population are sampled. The data that has been collected is analyzed using SPSS 20.0 software to test the validity and reliability, with the results of testing the validity and reliability tests showing valid and reliable reliability. Partial hypothesis testing where leadership style has a positive and significant effect on employee performance, and the compensation variable has a positive and significant effect on employee performance at PT. Pancaran Pondok Tering, on simultaneous hypothesis testing where leadership style and compensation have a positive and significant effect on the performance of PT. Radiant Pondok Tering. The value of the coefficient of determination obtained with statistical results is 0.771 or 77.1% so that the relationship between the independent variable and the dependent variable is very strong.